Sejarah Pembelajaran Al-Qur’an Di Masa Nabi Muhammad Saw - Abdul Jalil (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: This paper discusses the history of learning of the Koran before there is a mushhaf that is during the time of Prophet Muhammad, the pre-Islamic Arab society until the time of Prophet Muhammad was chosen by Allah to be Prophet dominated by oral culture. Therefore, the Prophet taught and transmitted the Qur'an by reading it directly to the companions (musyafahah), so even friends with the same method of teaching the Koran among others. At that time, the written Qur'an had no significant role in the process of learning the Koran. Dar al-Arqam and the house of the Prophet became a place of study of the Koran in the period of Mecca, while in the Medina period there were al-kuttab, shuffah, dar al-qurra 'and the mosque as the center or place of studying the Koran. Some Companions participated and assisted the Prophet in the task of teaching the Koran Keywords: Al-Quran, Learning, Prophet, Companions.